Reliability and Validity of Three Versions of the Brief Fear of Negative Evaluation Scale in Patients With Systemic Sclerosis: A Scleroderma Patient‐Centered Intervention Network Cohort Study. Issue 11 (26th October 2018) - Fox, Rina S.; Kwakkenbos, Linda; Carrier, Marie‐Eve; Mills, Sarah D.; Gholizadeh, Shadi; Jewett, Lisa R.; Roesch, Scott C.; Merz, Erin L.; Assassi, Shervin; Furst, Daniel E.; Gottesman, Karen; Mayes, Maureen D.; et al.
Abstract : Objective: Fear of negative evaluation is a common concern among individuals with visible differences but has received limited attention in systemic sclerosis (SSc), which can involve substantial changes to appearance. The Brief Fear of Negative Evaluation Scale (BFNE) was specifically designed to evaluate fear of negative evaluation. There are currently 3 versions of the BFNE with strong demonstrated measurement properties: two 8‐item versions (BFNE‐S, BFNE‐8) and one 12‐item version (BFNE‐II). The present study evaluated these versions in SSc, and identified the most appropriate version for use among SSc patients. Methods: Participants were 1, 010 patients with SSc enrolled in the Scleroderma Patient‐Centered Intervention Network cohort. Multiple group confirmatory factor analysis, Cronbach's alpha, and Pearson's product‐moment correlations were used to evaluate structural validity, internal consistency reliability, and convergent and divergent validity, respectively. Results: Confirmatory factor analysis demonstrated that 1‐factor models fit acceptably well for the 12‐item BFNE‐II, the 8‐item BFNE‐S, and the 8‐item BFNE‐8. Additionally, all Cronbach's alphas demonstrated excellent internal consistency reliability (BFNE‐II = 0.98, BFNE‐S = 0.97, BFNE‐8 = 0.96), and all versions had comparable associations with measures of social anxiety, body‐related attitudes, depression, age, and education. Conclusion: Psychometric support was found for all 3 versions of the BFNE, although the longer 12‐item BFNE‐II did not improve measurement compared to the shorter 8‐item versions (BFNE‐S and BFNE‐8). Of these 2, the BFNE‐S has been more widely studied, with strong validity data in a greater number of populations. Therefore, the BFNE‐S is recommended to assess fear of negative evaluation among patients with SSc.